Expandable Total Humeral Replacement in a Child with Osteosarcoma - Eric R. Henderson; Jidi Gao; John Groundland; Odion Binitie; G. Douglas Letson (Case Reports in Orthopedics)
Case. A right-handed 8-year-old female patient presented with a conventional, high-grade osteosarcoma involving her right humerus; through-shoulder amputation was recommended. After consultation, total humerus resection with expandable, total humeral endoprosthesis reconstruction was performed with a sleeve to encourage soft-tissue ingrowth. At three-year follow-up she has received one lengthening procedure and her functional scores are excellent. Conclusion. Total humeral resection and replacement in the pediatric population are rare and although early reports of expandable total humeral endoprosthesis outcomes demonstrate high failure rates, this patient’s success indicates that expandable total humeral replacement is a viable option.